Evaluation of the impact of net neutrality on the profitability of telecom operators: A game-theoretic approach - Marlies Van der Wee; Niels Vandevelde; Sofie Verbrugge; Mario Pickavet (International Telecommunications Society (ITS), 2015)
Net neutrality is defined as the concept in which Internet service providers are obliged to treat all data streams equally, independent of which application, service, device, sender or receiver is involved. They are as such forbidden to block, throttle or alter data traffic over their networks. The current debate about net neutrality raises important questions about if and how it should be implemented by law. This research summarizes the current regulations regarding net neutrality in the EU and US and finds significant differences, as well as specific cases where operators breached (or tried to breach) the concept of net neutrality. A case study about video on demand is used to analyze both these violations and certain approaches under net neutrality in order to see which scenario offers the greatest benefits, both from an operator's, as well as from a regulator's perspective. The results are computed using a game theoretic approach and from these results recommendations are subtracted that can be presented to regulators. The study finds that net neutrality can be enforced by law to prevent the decline of competition and innovation on the market.
Keywords: 330; net neutrality; game theory; telecommunications; congestion; video on demand; techno-economic analysis